Correlation between the Number of MSMEs and the Growth of the Workforce with the Regression Analysis Model - Hadigufri Triha; Alima Shofia; Ranti Mustika Putri; Mutia Alius; Trinda Farhan Satria (Journal of Computer Scine and Information Technology, 2023)
Unemployment at a young age is influenced by the Labor Force Participation Rate ( TPAK ). In addition, the Labor Force Participation Rate is also very influential on the economy in Indonesia. The thing that affects this TPAK is the ability of the region to create or produce jobs. Expansion of employment opportunities is also expected from the government to overcome this low Labor Force Participation Rate. Expansion of employment opportunities can be done by creating/developing programs that can support the hard skills and soft skills of the work force. The government can provide certified skills training that is recognized by companies. The government should encourage more young entrepreneurs to establish MSMEs (Micro, Small and Medium Enterprises) so that new job opportunities are also more open. The Covid-19 pandemic has made MSMEs play an important role in Indonesia's GDP with a contribution that reaches 61% and is able to absorb 97% of the workforce from the total absorption of the national workforce. Specifically for the City of Padang, based on the results of simple linear regression analysis, it was found that there is a strong relationship between the variable number of labor force and the number of MSMEs in Padang City where the conclusion of the regression statistics for multiple R is 0.82 which indicates that the independent variable (number of labor force) has a strong relationship with the dependent variable (number of SMEs). Based on the results of this simple linear regression test, it was found that R Square was worth 0.67. This shows that the resulting regression equation can be said to represent the existing conditions where y = 334333.21 - (0.67 * number of labor force). This can be seen from the R square value which is greater than 0.5 and close to 1